Therapeutic drug monitoring, electronic health records, and pharmacokinetic modeling to evaluate sirolimus drug exposure-response relationships in renal transplant patients - Zimmerman, Kanecia O. (Ther Drug Monit, 2016)
BACKGROUND: Sirolimus, an immunosuppressant agent used in renal transplantation, can prevent allograft rejection. Identification of the therapeutic index (ratio of minimum toxic concentration to minimum therapeutic concentration) for immunosuppresants is necessary to optimize the care of patients and set standards for bioequivalence evaluation of sirolimus products. However, the therapeutic index for sirolimus has been inconsistently defined, potentially due to inconsistencies in sirolimus exposure-response relationships. METHODS: The authors used retrospective therapeutic drug monitoring data from the electronic health records of patients treated in a tertiary healthcare system from 2008 to 2014, to: 1) develop a population pharmacokinetic model, 2) use the model to simulate sirolimus concentrations, and 3) characterize the exposure-response relationship. Using Wilcoxon rank-sum and Fisher’s exact tests, the authors determined relationships between sirolimus exposure and adverse events (anemia, leukopenia, thrombocytopenia, hyperlipidemia, decline in renal function) and the composite efficacy endpoint of graft loss or rejection. RESULTS: The developed 2-compartment population pharmacokinetic model showed appropriate goodness of fit. In a late-phase (>12 months), post-renal transplant population of 27 inpatients, the authors identified statistically significant relationships between 83 simulated peak and trough sirolimus concentrations and outcomes: graft loss or rejection (p=0.018), and decline in renal function (p=0.006), respectively. CONCLUSIONS: Use of therapeutic drug monitoring results and pharmacokinetic modeling permitted correlation of sirolimus concentrations with graft loss or rejection, and decline in renal function. However, the method was limited in its assessment of other adverse events. To better evaluate sirolimus exposure-response relationships, the method should be applied to a larger sample of newly-transplanted patients with a higher propensity toward adverse events or efficacy failure.